Specific Increase of Hippocampal Delta Oscillations Across Consecutive Treadmill Runs - Furtunato, Alan M. B.; Lobão-Soares, Bruno; Tort, Adriano Bretanha Lopes; Belchior, Hindiael (Frontiers in Behavioral Neuroscience, 2020)
Running speed affects theta (6-10 Hz) oscillations, the most prominent rhythm in the rat hippocampus. Many reports have found a strong positive correlation between locomotion speed and the amplitude and frequency of theta oscillations. However, less is known about how other rhythms are affected, and how consecutive runnings impact oscillatory activity in hippocampal networks. Here, we investigated whether the successive execution of short-term runnings modulates local field potentials (LFPs) in the rat hippocampus. To do this, we trained Long-Evans rats to perform voluntary 15-s runnings at 30 cm/s on a treadmill placed on the central stem of an eight-shape maze, in which they subsequently performed a spatial alternation task. We bilaterally recorded CA1 LFPs while rats executed at least 35 laps on the treadmill-maze apparatus. Within running periods, we observed progressive increases in delta band power (0.5-4 Hz) along with gradual decreases in theta band power across laps. A significant negative correlation in the power of these bands was observed along runnings. In addition, we found an increase in the interhemispheric phase coherence in the delta band, with no significant changes in the theta band. Our results thus show a differential modulation of delta and theta in CA1 LFPs while rats perform successive treadmill runnings at the same speed.